Pathogenesis of Japanese Encephalitis Virus Infection in a Golden Hamster Model and Evaluation of Flavivirus Cross-Protective Immunity - Bosco-Lauth, Angela (The American Society of Tropical Medicine and Hygiene, 2011)
Japanese encephalitis virus (JEV) is a mosquito-borne flavivirus endemic to Southeast Asia and surrounding Pacific Islands, and it has most recently emerged in northern Australia. JEV is closely related to West Nile virus (WNV) and St. Louis encephalitis virus (SLEV), both endemic to the United States. In the event that JEV is introduced into the Americas, it will be important to determine whether immunity to WNV or SLEV might afford protection from infection and development of viremia in susceptible hosts. We investigated a hamster model of JEV infection and showed that a large fraction of animals infected with either a genotype I or III isolate of virus developed viremia and encephalitic lesions without clinical signs of disease. Using this model, we showed that prior infection with WNV or SLEV, vaccination using a chimeric WNV vaccine, and passive immunization with anti-JEV immune sera prevented viremia in hamsters challenged with JEV.